2006
DOI: 10.1016/j.micres.2005.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Acid response of exponentially growing Escherichia coli K-12

Abstract: Induction of acid tolerance response (ATR) of exponential-phase Escherichia coli K-12 cells grown and adapted at different conditions was examined. The highest level of protection against pH 2.5 challenges was obtained after adaptation at pH 4.5-4.9 for 60 min. To study the genetic systems, which could be involved in the development of log-phase ATR, we investigated the acid response of E. coli acid resistance (AR) mutants. The activity of the glutamate-dependent system was observed in exponential cells grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 31 publications
1
29
0
2
Order By: Relevance
“…Repression of RpoS had no effect on the survival of cells adapted in oxalate, and deletion of the rpoS gene did not increase cell susceptibility to acid as it does for the oxidative AR1 and amino-aciddependent systems AR2 and AR3 (3,5). In addition, our deletion data show that knockout of YdeO, GadX, and GadW had no significant effect on the oxalate-dependent ATR in stationary-phase E. coli cells (Fig.…”
Section: ϫ5mentioning
confidence: 61%
“…Repression of RpoS had no effect on the survival of cells adapted in oxalate, and deletion of the rpoS gene did not increase cell susceptibility to acid as it does for the oxidative AR1 and amino-aciddependent systems AR2 and AR3 (3,5). In addition, our deletion data show that knockout of YdeO, GadX, and GadW had no significant effect on the oxalate-dependent ATR in stationary-phase E. coli cells (Fig.…”
Section: ϫ5mentioning
confidence: 61%
“…6A). For the same reason and to facilitate a better comparison, the ATR was also performed in LB medium (49,50) (Fig. 6A).…”
Section: Resultsmentioning
confidence: 99%
“…The DNA damage in the purA and purB mutants was higher than that in the wild type. These results demonstrated that metabolic processes that require ATP participate in survival under extremely acidic conditions, and that one such system is the ATP-dependent DNA repair system.Since the normal human stomach averages pH 2 for approximately 2 h after it becomes empty, to survive in the mammalian host both commensal and pathogenic enteric bacteria have resistance systems to protect themselves against acidic stress (5,32,36).Four acidic resistance (AR) systems that are induced under different conditions have been proposed for Escherichia coli (5). Acidic resistance system 1 (AR1), which is induced in cells grown to stationary phase in a moderately acidic medium, requires the sigma factor RpoS (3, 27) and the cyclic AMP receptor protein CRP (2).…”
mentioning
confidence: 99%
“…Since the normal human stomach averages pH 2 for approximately 2 h after it becomes empty, to survive in the mammalian host both commensal and pathogenic enteric bacteria have resistance systems to protect themselves against acidic stress (5,32,36).…”
mentioning
confidence: 99%